Stories in midwifery: Reflection, Inquiry, Action - Cummins, Allison; Gillett, Katharine; McLaughlin, Karen; Musgrave, Loretta; Wood, Jessica (ELSEVIER, 2023)
This insightful book and accompanying video resource present a collection of perspectives relating to different issues around birthing and midwifery. Through the voices of mothers, midwives, students, health professionals and family members, you will build empathy and understanding, reflect, and learn to apply innovative approaches in your own practice. The book covers a range of topics, such as midwifery continuity of care, place of birth, multiple pregnancy, complex pregnancies, congenital birth abnormalities, supporting culturally and linguistically diverse women, anxiety and depression, and working with women with physical and/or intellectual disabilities.